Naming food in English in multilingual Cameroon - Anchimbe, Eric (Talking about Food : The social and the Global in Eating Communities, 2020)
Naming food in a nativised variety of English in a densely multilingual context like Cameroon is a complex phenomenon. This is because certain foods or dishes carry sociocultural significations that may be lost or altered if their original names are translated or abandoned for others. Using data from the food blog , this paper explains the word formation processes used and the social meanings embedded in food names in Cameroon English (CamE). Borrowing and compounding emerge as the most common processes, although there are a few cases of metaphorical extension. The data is analysed using the competition and selection hypothesis (Mufwene 2001) and the framework of filtration processes (Anchimbe 2006), both anchored in the World Englishes paradigm.